Ferroptosis as an emerging therapeutic target in liver diseases - Lu, Yuzhen; Hu, Junjie; Chen, Liang; Li, Shan; Yuan, Ming; Tian, Xianxiang; Cao, Peng; Qiu, Zhenpeng (Frontiers in Pharmacology, 2023)
Ferroptosis is an iron-dependently nonapoptotic cell death characterized by excessive accumulation of lipid peroxides and cellular iron metabolism disturbances. Impaired iron homeostasis and dysregulation of metabolic pathways are contributors to ferroptosis. As a major metabolic hub, the liver synthesizes and transports plasma proteins and endogenous fatty acids. Also, it acts as the primary location of iron storage for hepcidin generation and secretion. To date, although the intricate correlation between ferroptosis and liver disorders needs to be better defined, there is no doubt that ferroptosis participates in the pathogenesis of liver diseases. Accordingly, pharmacological induction and inhibition of ferroptosis show significant potential for the treatment of hepatic disorders involved in lipid peroxidation. In this review, we outline the prominent features, molecular mechanisms, and modulatory networks of ferroptosis and its physiopathologic functions in the progression of liver diseases. Further, this review summarizes the underlying mechanisms by which ferroptosis inducers and inhibitors ameliorate liver diseases. It is noteworthy that natural active ingredients show efficacy in preclinical liver disease models by regulating ferroptosis. Finally, we analyze crucial concepts and urgent issues concerning ferroptosis as a novel therapeutic target in the diagnosis and therapy of liver diseases.